„MEMORY OF CULTURE" AS FACTOR OF AUTOCOMMUNICATION „ME OF WRITER" AND „ME OF RESEARCHER": PHENOMENON OF CREATIVE INDIVIDUALITY OF VALERY SHEVCHUK - Soletsky, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article deals with the phenomenon of Valery Shevchuk"s creative individuality, including mutual transitivity and interdependence of scientific and artistic ways of thinking, literary and research experience. Auto-communication of a researcher and a writer demonstrates the importance of the experience of Baroque culture in cognitive and creative interpretations.